Association of plasma EFEMP1 with brain aging and dementia: Biomarkers (non‐neuroimaging) / Novel biomarkers. (7th December 2020) - McGrath, Emer R; Himali, Jayandra J; Levy, Daniel; Yang, Qiong; DeCarli, Charles; Courchesne, Paul; Satizabal, Claudia L; Finney, Rebecca; Vasan, Ramachandran S; Beiser, Alexa S; Seshadri, Sudha
Abstract: Background: Biological pathways underlying the association between white matter hyperintensities (WMH) and Alzheimer's disease (AD) dementia remain poorly understood. Epidermal growth factor containing fibulin extracellular matrix protein‐1 (EFEMP1) has been associated with increased WMH burden and disorders of premature aging. However, it is unknown if elevated circulating EFEMP1 is associated with clinical dementia. We determined the association between plasma EFEMP1 levels and incident dementia and Alzheimer's disease (AD) dementia in a community‐based sample of cognitively healthy individuals. Method: Plasma EFEMP1 levels were measured in 1597 [53% women, mean age 68.7 (SD 5.7) yr] Framingham Heart Study Offspring cohort participants who were free of dementia at examination cycle seven (1998‐2001). We related plasma EFEMP1 levels to risk of incident dementia and Alzheimer's disease (AD) dementia. Structural MRI brain measures and neurocognitive test performance were included as secondary outcomes. Result: During a median 11.8 [Q1, Q3: 7.1, 13.3] year follow‐up, 131 participants developed dementia and 98 were diagnosed with AD dementia. On Cox proportional‐hazards analysis adjusting for vascular risk factors and ApoE4 carrier status, the highest quintile of plasma EFEMP1, compared to the bottom four quintiles, was associated with an almost 80% increased risk of time to incident all‐cause dementia (HR 1.77, 95% CI 1.18‐2.64) and AD dementia (HR 1.76, 95% CI 1.11‐2.81). The highest quintile of EFEMP1, compared to the bottom four quintiles, was also associated with lower total brain volume (SE, ‐0.28±0.11, p=0.01) and hippocampal volume (‐0.006±0.003, p=0.04) but not WMH burden. Higher circulating EFEMP1 concentrations were associated with impairment in abstract reasoning (Similarities test, ‐0.18±0.08, p=0.018 per standard deviation increment in EFEMP1). Conclusion: Elevated circulating EFEMP1 levels are associated with an increased risk of incident dementia and AD dementia as well as lower brain volumes and impaired cognitive performance. EFEMP1 may play an important biological role in the development of AD and all‐cause dementia mediated through nonvascular pathways (e.g. microglial activation or via regulatory effects on metalloproteases), although additional studies are warranted to replicate our findings.